2010
DOI: 10.1002/humu.21289
|View full text |Cite
|
Sign up to set email alerts
|

Short rare MUC6 minisatellites-5 alleles influence susceptibility to gastric carcinoma by regulating gene

Abstract: The human MUC6 gene, which is reported to be expressed in the stomach and gall bladder, is clustered on chromosome 11p15.5 with other secreted mucins. In this study, the genomic structure of MUC6 has been analyzed and five VNTR (minisatellites; MS1-MS5) were identified. These minisatellites were analyzed in genomic DNA extracted from 1,103 controls, 470 gastric cancer patients, and multigenerational families. Five novel minisatellites were found to be polymorphic and transmitted through meiosis by Mendelian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
1
26
1
Order By: Relevance
“…Several previous studies have identified an association between cancer predisposition and minisatellites (Leem et al, 2002;Leem et al, 2004;Jeong et al, 2007;Seol et al, 2008;Yoon et al, 2008;Lee et al, 2009;Kwon et al, 2010). Some minisatellite alleles are associated with human disease and with differential expression of nearby genes (Davidson and Britten, 1979).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several previous studies have identified an association between cancer predisposition and minisatellites (Leem et al, 2002;Leem et al, 2004;Jeong et al, 2007;Seol et al, 2008;Yoon et al, 2008;Lee et al, 2009;Kwon et al, 2010). Some minisatellite alleles are associated with human disease and with differential expression of nearby genes (Davidson and Britten, 1979).…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between rare length HRAS minisatellite alleles and cancer risk were implicated by case-control studies (Krontiris et al, 1993;Bennett et al, 1995;Fiskerstrand et al, 1999;MacKenzie and Quinn, 1999). Especially, rare alleles of VNTR are associated with a high risk of various types of cancer (Leem et al, 2002;Leem et al, 2004;Jeong et al, 2007;Seol et al, 2008;Yoon et al, 2008;Lee et al, 2009;Kwon et al, 2010). To ascertain minisatellite influence on gene expression, we examined the effects of flanking luciferase reporter genes with minisatellites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant MUC6 expression was often found in gastrointestinal diseases, in relation to MUC6-MS5 and susceptibility to rectal cancers [116]. MUC6-MS5 sequences with different sizes were found to contain several putative transcription factors binding sites for Hnf4, Maz, E2f1, Pbx, Tal, Bach2 and Krox [115]. Ahn et al [116] suggested that loci of MUC6 MSs may function as a useful predisposition marker of rectal cancer risk particularly to the male gender.…”
Section: Rectal Cancermentioning
confidence: 97%
“…Among these, gastric mucin MUC6 has a role in gastric cancer development [52] and is aberrantly expressed during the progression of some colorectal cancers [114]. MUC6 has five novel tandem repeats (TR) (MUC6-(minisatellite, MS) MS1, -MS2, -MS3, -MS4, -MS5) in intronic regions [115]. Aberrant MUC6 expression was often found in gastrointestinal diseases, in relation to MUC6-MS5 and susceptibility to rectal cancers [116].…”
Section: Rectal Cancermentioning
confidence: 99%